2005
DOI: 10.1167/5.10.7
|View full text |Cite
|
Sign up to set email alerts
|

Focus cues affect perceived depth

Abstract: Depth information from focus cues--accommodation and the gradient of retinal blur--is typically incorrect in three-dimensional (3-D) displays because the light comes from a planar display surface. If the visual system incorporates information from focus cues into its calculation of 3-D scene parameters, this could cause distortions in perceived depth even when the 2-D retinal images are geometrically correct. In Experiment 1 we measured the direct contribution of focus cues to perceived slant by varying indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
235
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 279 publications
(257 citation statements)
references
References 111 publications
6
235
1
Order By: Relevance
“…The results of Experiment 3 suggest that accommodative blur contributes to the perception of slant; when it was removed from the observers' retinal images, their perception of the surface slant decreased (see Figure 11). Our results are thus consistent with those of Ciuffreda et al (2007), Frisby et al (1995), and Watt et al (2005), who suggested that retinal blur serves as an important source of information supporting the perception of surface slant and depth.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results of Experiment 3 suggest that accommodative blur contributes to the perception of slant; when it was removed from the observers' retinal images, their perception of the surface slant decreased (see Figure 11). Our results are thus consistent with those of Ciuffreda et al (2007), Frisby et al (1995), and Watt et al (2005), who suggested that retinal blur serves as an important source of information supporting the perception of surface slant and depth.…”
Section: Discussionsupporting
confidence: 92%
“…Given that our surfaces were physically slanted in depth (instead of being simulated computationally and then displayed on a frontoparallel monitor or projection screen), it is possible that other monocular factors, such as accommodative blur (Ciuffreda, Wang, & Vasudevan, 2007;Frisby, Buckley, & Horsman, 1995;Watt, Akeley, Ernst, & Banks, 2005), contributed to the accurate performance of our observers in Experiment 1. Gibson (1950b) acknowledged the possibility that differential blur might contribute to the perception of slant; he stated that "differential blur might be .…”
Section: Methodsmentioning
confidence: 99%
“…Only one conventional cue 30 (shading) specifies a 3-D shape in the image shown in Figure 20, but it is a cue that is generally regarded to be significantly less reliable than binocular disparity (Bülthoff & Mallot, 1988;Vuoung, 55 . Moreover, recent statistical models of depth cue integration posit the existence of a "flatness prior" which claims that the visual system is biased towards inferring flat frontoparallel surfaces in the presence of unreliable or conflicting depth cues (Adams & Mammasian, 2004;Domini, Shah & Caudek, 2011;Watt et al, 2005;Young et al, 1993). Since the majority of cues, including the most reliable one (disparity), specify a flat surface, it would be difficult for cue integration models to adequately explain why we perceive a 3-D object instead of a flat patterned surface.…”
Section: Seeing Depth In the Absence Of Stereopsismentioning
confidence: 99%
“…The retinal image blur effect refers to the phenomena associated with eye accommodation change in which objects away from the eye's accommodative distance appear blurry in the retinal image due to the limited depth-of-field (DOF) of the eyes. The conventional S3D displays fail to render correct retinal blur effects and stimulate natural eye accommodation response, which causes several cue conflicts and is considered as one of the key contributing factors to various visual artifacts associated with viewing S3D displays, such as distorted depth perception [3] and visual discomfort [4]. In recent years, several display methods that are potentially capable of resolving the VAC problem have been demonstrated, including holographic displays [5], volumetric displays [6,7], multi-focal plane displays [8][9][10] and light field displays [11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%